Human T‐cell leukemia virus type 1 Tax oncoprotein represses the expression of the BCL11B tumor suppressor in T‐cells. Issue 4 (16th March 2015) - Takachi, Takayuki; Takahashi, Masahiko; Takahashi‐Yoshita, Manami; Higuchi, Masaya; Obata, Miki; Mishima, Yukio; Okuda, Shujiro; Tanaka, Yuetsu; Matsuoka, Masao; Saitoh, Akihiko; Green, Patrick L.; Fujii, Masahiro
Abstract : Human T‐cell leukemia virus type 1 (HTLV‐1) is the etiological agent of adult T cell leukemia (ATL), which is an aggressive form of T‐cell malignancy. HTLV‐1 oncoproteins, Tax and HBZ, play crucial roles in the immortalization of T‐cells and/or leukemogenesis by dysregulating the cellular functions in the host. Recent studies show that HTLV‐1‐infected T‐cells have reduced expression of the BCL11B tumor suppressor protein. In the present study, we explored whether Tax and/or HBZ play a role in downregulating BCL11B in HTLV‐1‐infected T‐cells. Lentiviral transduction of Tax in a human T‐cell line repressed the expression of BCL11B at both the protein and mRNA levels, whereas the transduction of HBZ had little effect on the expression. Tax mutants with a decreased activity for the NF‐κB, CREB or PDZ protein pathways still showed a reduced expression of the BCL11B protein, thereby implicating a different function of Tax in BCL11B downregulation. In addition, the HTLV‐2 Tax2 protein reduced the BCL11B protein expression in T‐cells. Seven HTLV‐1‐infected T‐cell lines, including three ATL‐derived cell lines, showed reduced BCL11B mRNA and protein expression relative to an uninfected T‐cell line, and the greatest reductions were in the cells expressing Tax. Collectively, these results indicate that Tax is responsible for suppressing BCL11B protein expression in HTLV‐1‐infected T‐cells; Tax‐mediated repression of BCL11B is another mechanism that Tax uses to promote oncogenesis of HTLV‐1‐infected T‐cells. Abstract : We found that HTLV‐1 oncoprotein Tax represses the expression of the tumor suppressor BCL11B, indicating that Tax‐mediated repression of BCL11B is a mechanism promoting leukemogenesis.